2019
DOI: 10.3390/en12040701
|View full text |Cite
|
Sign up to set email alerts
|

Glazing Sizing in Large Atrium Buildings: A Perspective of Balancing Daylight Quantity and Visual Comfort

Abstract: Due to the multiple benefits on energy, well-being, comfort, and the economy, the utilization of daylight remains an imperative topic of architectural design. With the remarkable ability of drawing and increasing daylight deep into the core of buildings, atriums with a large proportion of glazing have become one of the most preferred design forms. The concomitant and unexpected visual discomfort in modern buildings, however, has drawn increasing concerns. Therefore, this study investigated the relation between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…The latest method for evaluating daylight performance is climate-based daylight modeling (CBDM), which is a dynamic method based on real daylight climate data hour by hour throughout the year, making daylight simulation more accurate and reliable. CBDM provides various metrics for evaluating daylight performance, such as spatial daylight autonomy (sDA), annual sunlight exposure (ASE), and useful daylight illuminance (UDI) [5][6][7]12,13,30,31]. Therefore, the Shandong Jinan (CSWD) file downloaded from https://energyplus.net/weather (accessed on 23 November 2021) serves as the weather file for the later daylight simulation study.…”
Section: Research Methodology and Model Buildingmentioning
confidence: 99%
See 1 more Smart Citation
“…The latest method for evaluating daylight performance is climate-based daylight modeling (CBDM), which is a dynamic method based on real daylight climate data hour by hour throughout the year, making daylight simulation more accurate and reliable. CBDM provides various metrics for evaluating daylight performance, such as spatial daylight autonomy (sDA), annual sunlight exposure (ASE), and useful daylight illuminance (UDI) [5][6][7]12,13,30,31]. Therefore, the Shandong Jinan (CSWD) file downloaded from https://energyplus.net/weather (accessed on 23 November 2021) serves as the weather file for the later daylight simulation study.…”
Section: Research Methodology and Model Buildingmentioning
confidence: 99%
“…At present, atriums have become a trend in modern commercial design because they absorb natural light and connect adjacent spaces with the outside world [10]. Numerous studies have demonstrated the use of natural daylight in commercial spaces to increase sales performance and office rental value, improve building users' health, and enhance customer satisfaction [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Energy saving potentials and occupants well-being, health, mood, and productivity are strongly influenced by daylight availability into buildings and thus a careful design of city shape could improve visual comfort in indoors and simultaneously reduce electrical energy consumption [218,219]. On the other hand, modelling of artificial lighting generally leans on different software such as DIALux [220] and Relux [221] which are used for indoors but even street lighting design.…”
Section: Environmental Comfort Inferencementioning
confidence: 99%
“…Glazing systems make it possible to benefit from solar heat gains and daylight, other than providing occupants a view of the outdoor environment. However, they can lead to excessive heat gains and visual discomfort (glare and asymmetrical daylight distribution) for the occupants [1][2][3][4]. Recent buildings, namely, commercial ones, are built with high window to wall ratios, having in mind potential energy savings in artificial lighting, apart from the esthetic design [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%